ANALISIS INDEKS NEGARA HUKUM INDONESIA - Riani Bakri; Murtir Jeddawi (Jurnal Pallangga Praja (JPP), 2022)
In fact, all countries claim to be a state of law. Country by regulation. even so, it was found empirically thatimplementation as a state is based on laws/rules that distinguish one legal state from another. The Unitarystate of the Republic of Indonesia, in accordance with article 1 paragraph (3) of the 1945 Constitution,expressly states that Indonesia is a state based on law, not a state based on power. To see the extent to whichthe existence of the state of Indonesia as a rule of law can be seen in the Index of the state of Law of Indonesia.from a review of the Indonesian rule of law index document, the sub-indicators show an increasing sub-indexindicator, but other sub-indicators show an increasing trend. although comprehensively the Indonesian rule oflaw index has increased in value even though it is not optimal.